Secure Data Management 8th VLDB Workshop, SDM 2011, Seattle, WA, USA, September 2, 2011, Proceedings - Jonker, Willem; Petkovic, Milan; SpringerLink (Online service). (aBerlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 8th VLDB Workshop on Secure Data Management held in Seattle,WA, USA in September 2, 2011 as a satellite workshop of the VLDB 2011 Conference . The 10 revised full papers presented were carefully reviewed and selected from 19 submissions. The papers are organized in topical sections on privacy protection and quantification, security in cloud and sensor networks and secure data managment technologies.
Electronic reproduction.
Keywords: Database security -- Congresses; Computers -- Access control -- Congresses; Data encryption (Computer science) -- Congresses; Data protection -- Congresses; Database management -- Congresses; Electronic books